“Among Us, Whoever Circumvents Taxation Laws Best is Considered Shrewder”: Illegal Practices and Tax System in the Sovereign State of Bolívar, 1857-1886 - Flórez Bolívar, Roicer Alberto (Sociedad y Economía, 2012)
This article analyzes the illicit practices used by citizens of the Sovereign State of Bolivar between 1857 and 1886 to avoid state taxes. Similarly, it shows how such practices affected the functioning of the state’s public administration. The main idea supported in this analysis is that among the factors that contributed to the economic instability experienced by the Sovereign State of Bolivar, citizens tax evasion was one of the most significant, seriously affecting the functioning of public administration, since the most representative state taxes (cattle slit, income tax, distillation of spirits, and consumption of foreign goods) were the ones most frequently evaded.